Biodegradable pot from oil palm fronds waste: production process, physical properties, and biodegradability study - Jaka Darma Jaya; Abdul Majid; Nuryati Nuryati; Yuliana Ningsih (AGROINTEK, 2024)
This research investigated the potential use of oil palm frond waste as a new raw material for developing biodegradable pots (biopot), which could substitute planting containers made from petroleum-based materials such as pots or plastic polybags. This study was aimed, in particular, at examining the physical characteristics and biodegradability of biopot products. This objective was essential for ensuring that the functionality, characteristics, and biodegradability of biopots were technically acceptable for their agricultural application. Production of biopot was done by cold pressing method, which started by mixing the frond fibers as reinforcement with tapioca as a matrix and molding it using the cold pressing method. Furthermore, testing of physical characteristics includes density, moisture content, water absorption, and biodegradability in soil media. The research shows that the biopot from oil palm fronds has a density of 0.27-0.44 g / cm3, moisture content of 1.28-4.71%, and water absorption of 179.88-285.74%. The degradability of biodegradable pots ranged from 11.07-34.22%. Based on the above characteristics, the biodegradable pot from oil palm fronds has the potential to be used for planting containers. Biopot from oil palm fronds was interesting to develop since it performed suitable characteristics, compared to the Indonesian National Standard (SNI) of the similar composites product and the characteristics of biodegradable pot from other previous reliable research